2012
DOI: 10.5551/jat.9621
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Calcitriol Decreases Aortic Renin, Blood Pressure, and Atherosclerosis in Apoe-Null Mice

Abstract: Aims:To determine whether low-dose calcitriol attenuates atherosclerosis in apoE-null mice and, if so, through which predominant mechanism. Methods: Starting at the age of 6 weeks, mice received intraperitoneal injections of either 0.25 ng/g body weight of calcitriol or the vehicle, every other day for 8 weeks.Results: Calcitriol treatment resulted in 35% reduction of atherosclerosis at the aortic sinus, and in a significant decrease in blood pressure. These effects were possibly mediated by downregulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…In epidemiologic studies, a link was found between vitamin D deficiency and atherosclerotic cardiovascular disease (Dobnig et al, 2008;Giovannucci et al, 2008). In apolipoprotein E knockout mice, 1,25D 3 administration induced a marked reduction in the formation of atherosclerotic lesions (Takeda et al, 2010;Ish-Shalom et al, 2012). In these studies, 1,25D 3 was shown to prevent the development of atherosclerosis by changing the function or differentiation of dendritic cells and regulatory T cells (Takeda et al, 2010) or by downregulation of the renin-angiotensin system (Ish-Shalom et al, 2012).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…In epidemiologic studies, a link was found between vitamin D deficiency and atherosclerotic cardiovascular disease (Dobnig et al, 2008;Giovannucci et al, 2008). In apolipoprotein E knockout mice, 1,25D 3 administration induced a marked reduction in the formation of atherosclerotic lesions (Takeda et al, 2010;Ish-Shalom et al, 2012). In these studies, 1,25D 3 was shown to prevent the development of atherosclerosis by changing the function or differentiation of dendritic cells and regulatory T cells (Takeda et al, 2010) or by downregulation of the renin-angiotensin system (Ish-Shalom et al, 2012).…”
Section: Introductionmentioning
confidence: 89%
“…In apolipoprotein E knockout mice, 1,25D 3 administration induced a marked reduction in the formation of atherosclerotic lesions (Takeda et al, 2010;Ish-Shalom et al, 2012). In these studies, 1,25D 3 was shown to prevent the development of atherosclerosis by changing the function or differentiation of dendritic cells and regulatory T cells (Takeda et al, 2010) or by downregulation of the renin-angiotensin system (Ish-Shalom et al, 2012). 1,25D 3 suppresses renin gene expression by blocking the binding of cAMP response element-binding protein to cAMP response element in the promoter of the gene (Yuan et al, 2007) and thereby reduces the production of angiotensin II, a potent proatherogenic peptide.…”
Section: Introductionmentioning
confidence: 99%
“…There were thus 4 experimental groups, each comprising approximately 20 mice. At the age of 8 weeks, noninvasive basal blood pressure was obtained as described [12], and animals were switched to a high fat Western diet (Teklad diet 88317, Harlan, Madison, WI) for 8 weeks. L-NAME administration was continued throughout the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Quantification of the plaques was performed using a digital imaging processing program (NIS element Br 3.0 imaging system) (Nikon Instruments Europe B.V., The Netherlands), as described [12]. …”
Section: Methodsmentioning
confidence: 99%
“…By deleting VDR gene in LDLr − / − mice, Szeto and coworkers firstly suggested that inhibition of macrophage VDR signalling in atherosclerotic mice also suppressed the RAAS [100]. Further studies by Ish-Shalom and colleagues and Weng and coworkers have recently supported these findings in mice [148, 149]. In addition, the discovery of fibroblast growth factor (FGF)23/klotho axis has also broadened the potential role of vitamin D on the endocrine signalling in the pathogenesis of atherosclerosis.…”
Section: The Intraplaque Pathophysiological Activity Of Vitamin D mentioning
confidence: 99%